The UN International Legal Standards Related to Equality Between Women and Men as a Factor Affecting Gender Education Development in the Post-Soviet Space - Гришак, Світлана Миколаївна (Pedagogy of Higher and Secondary Education, 2017)
In the article the UN international legal standards related to equality between women and men are examined as a factor affecting gender education development in the countries of post-soviet space. The observance of international legal standards of equality between women and men has acquired special urgency for the newly formed States as they embarked on the democratic path of development, and focused on the European and world educational space integration. International legal standards related to equality of women and men are defined as the specific international legal regulations in the field of gender equality, which include international instruments, conventions, declarations, resolutions, covenants and the like. They serve as a model for the regulation of the individual rights and freedoms in national law and legislation.It is established that the United Nations international legal instruments, which are advisory in nature, form the universal international legal standards in the field of equality between women and men, including education. They are «Universal Declaration of Human Rights» (1948), «Declaration on the Elimination of Discrimination Against Women» (1967), «Declaration on the Elimination of Violence Against Women» (1993) and some convention documents («International Covenant on Economic, Social and Cultural Rights»,1966; «The Convention on the Elimination of All Forms of Discrimination Against Women», CEDAW, 1979; etc.). To affect gender education development there have been proved The UN international legal standards related to equality between women and men. The legal regulation of gender relations implies protection of rights and provision of equal access to education by any person regardless of gender; the elimination of all forms of discrimination against women; the right to obtain qualitative education by women and girls; reduction of gender gap at all levels of education, particularly higher and the like as well as the requirement to take the necessary measures to change harmful cultural stereotypes of public consciousness and behaviour that is only possible through the dissemination of gender knowledge among the population of post-Soviet countries.